2017
DOI: 10.1142/s2010135x17500436
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and dielectric properties of Fe3BO6 nanoplates prepared through self-combustion method

Abstract: In the present investigation, a facile synthesis method is explored involving a self-combustion of a solid precursor mixture of iron oxide Fe 2 O 3 and boric acid (H 3 BO 3 ) using camphor (C 10 H 16 O) as fuel in ambient air in order to form a single phase Fe 3 BO 6 crystallites. X-ray diffraction (XRD), Field emission electron microscopy (FESEM), magnetic, and dielectric properties of as prepared sample are studied. From XRD pattern, a single phase compound is observed with an orthorhombic crystal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It was observed that π-YBO3 doped with Mn 2+ exhibited ferroelectric polarization, with Pr ≈ 9.52 × 10 -2 µC/cm 2 as the P-E loop's remnant polarisation value. The iron-doped sample also displayed ferroelectric polarization, with a remnant polarization value of 1.90 × 10 -1 at zero electric fields [37,42] .…”
Section: Ferroelectric Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that π-YBO3 doped with Mn 2+ exhibited ferroelectric polarization, with Pr ≈ 9.52 × 10 -2 µC/cm 2 as the P-E loop's remnant polarisation value. The iron-doped sample also displayed ferroelectric polarization, with a remnant polarization value of 1.90 × 10 -1 at zero electric fields [37,42] .…”
Section: Ferroelectric Propertiesmentioning
confidence: 98%
“…Figure 7(c) shows iron-doped samples' magnetization versus magnetic field. A small hysteresis loop suggests the presence of antiferromagnetic ordering in the sample at 300 K [37] . The magnetic susceptibility of π-Y0.90Fe0.10BO3 under ZFC and FC conditions has been presented in Figure 7(d).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Iron oxyborate (Fe3BO6) has been used in ceramics (1), drugs, pigments, gas sensors, catalysts (2), electrodes and biological probes because of magnetic (3,4), dielectric (5), conductivity (6), optical (7), structural (8), electrochemical (9) and surface properties. It is a promising anode material in lithium-ion batteries with high reversible capacity (10), unremarkable toxicity and low cost and it is also used in sodium ion batteries with high activity (11).…”
Section: Introductionmentioning
confidence: 99%